The relationship between keratin 18 and epithelial-derived tumors: as a diagnostic marker, prognostic marker, and its role in tumorigenesis - Yan, Jiazhi; Yang, Aiwei; Tu, Shuo (Frontiers in Oncology, 2024)
As a structural protein, keratin is mainly expressed in epithelial cells and skin appendages to provide mechanical support and external resistance. The keratin family has a total of 54 members, which are divided into type I and type II. Two types of keratins connect to each other to form keratin intermediate filaments and participate in the construction of the cytoskeleton. K18 is a non-hair keratin, which is widely expressed in simple epithelial tissues with its partner, K8. Compared with mechanical support, K8/K18 pairs play more important roles in biological regulation, such as mediating anti-apoptosis, regulating cell cycle progression, and transmitting signals. Mutations in K18 can cause a variety of non-neoplastic diseases of the visceral epithelium. In addition, the expression levels of K18 are frequently altered in various epithelial-derived tumors, especially adenocarcinomas, which suggests that K18 may be involved in tumorigenesis. Due to the specific expression pattern of K18 in tumor tissues and its serum level reflecting tumor cell death, apply K18 to diagnose tumors and predict its prognosis have the potential to be simple and effective alternative methods. However, these potential roles of K18 in tumors have not been fully summarized. In this review, we focus on the relationship between K18 and epithelial-derived tumors, discuss the value of K18 as a diagnostic and prognostic marker, and summarize the interactions of K18 with various related proteins in tumorigenesis, with examples of simple epithelial tumors such as lung, breast, liver, and gastrointestinal cancers.